Regulation of phagocytosis by Rho GTPases - Mao, Yingyu (Small GTPases, 2015)
Phagocytosis is defined as a cellular uptake pathway for particles of greater than 0.5 μm in diameter. Particle clearance by phagocytosis is of critical importance for tissue health and homeostasis. The ultimate goal of anti-pathogen phagocytosis is to destroy engulfed bacteria or fungi and to stimulate cell-cell signaling that mount an efficient immune defense. In contrast, clearance phagocytosis of apoptotic cells and cell debris is anti-inflammatory. High capacity clearance phagocytosis pathways are available to professional phagocytes of the immune system and the retina. Additionally, a low capacity, so-called bystander phagocytic pathway is available to most other cell types. Different phagocytic pathways are stimulated by particle ligation of distinct surface receptors but all forms of phagocytosis require F-actin recruitment beneath tethered particles and F-actin re-arrangement promoting engulfment, which are controlled by Rho family GTPases. The specificity of Rho GTPase activity during the different forms of phagocytosis by mammalian cells is the subject of this review.